Current Standing and Technical Guidance on Intracellular Drug Quantification: A New Site Specific Bioavailability Prediction Approach. (2nd January 2020) - Jadav, Tarang; Jain, Sonali; Kalia, Kiran; Sengupta, Pinaki
Abstract: Determination of intracellular concentration becomes essential for the drugs having target receptors or bioactivation site inside the cells. Majority of the antiviral drugs are nucleoside analogs and their intracellular phosphorylated metabolites are active. The anticancer drugs of the cellular enzyme and nucleoside analog category are also required to be undergone intracellular drug level analysis. In this review, we have sequentially described the cell isolation protocols, cell lysis techniques and sample preparation approach to be followed for quantification of intracellular levels of selected antiviral and anticancer drugs. Major limitations for intracellular analyte quantification and their possible way out has been discussed. Currently, no literature is available summarizing these important aspects including bioanalysis of intracellular quantification of either antiviral or anticancer drugs. This review, thus, can be considered to be first of its kind and will be highly useful in providing guidance for intracellular drug analysis aiming determination of the site-specific bioavailability.